Meat characteristics of bunaji, gudali and keteku breeds of cattle (2004)
Carcass and meat quality traits of three breeds of cattle, which include Bunaji, Gudali and Keteku, were investigated. A total of five animals per breed were used for the study. The mean ages and live weights were not significantly different. Also, the mean carcass weight did not differ (p>0.05) significantly. The dressing percentage for Bunaji was lower (p<0.05) than for Gudali and Keteku. Back fat thickness was significantly higher (p<0.05) for Keteku and Bunaji than for Gudali while the rib eye area that was measured on the longissimus dorsi was higher in Keteku with 50cm2 while Gudali and Bunaji had 41cm2 and 33cm2 respectively. Texture of the lean meat was scored highest (p<0.05) in Gudali, followed by Bunaji while the least score was recorded for Keteku. However, the meat colour and marbling scores were not different (p>0.05) across the breeds. Shear force and cooking loss were least (p<0.05) in Keteku while Bunaji and Gudali had similar values (p>0.05) for both traits respectively.